(untitled) (The Research of Medical Science Review, 2025)
The introduction of ileostomy has facilitated lower pelvic anastomosis. Many complications can occur after ileostomy closure. Wound infection and cosmetic problems are common after reversal of ileostomy. Objective of the study was to compare the frequency of satisfaction with cosmetic effects between linear versus purse-string skin closure after a loop ileostomy reversal. The study design was Randomized controlled trail, conducted at In-patient surgical department, DHQ Gujranwala, from 30 June, 2024 to 29 December, 2024. Total of 60 (30 in each group) patients undergoing ileostomy reversal was enrolled in the study. Two groups were made as follows; Group-A; Linear skin closure Group-B; Purse-string skin closure Satisfaction with cosmetic effect was found in 21 out of 30 (70%) cases in Group-A (Linear skin closure) and in 28 out of 30 (93.3%) cases in Group-B (Purse string closure) (p=0.04). Wound infection occurred in 08 out of 30 (26.7%) cases in Group-A (Linear skin closure) and in 03 out of 30 (10%) cases in Group-B (Purse string closure) (p=0.18). So we concluded that satisfaction with cosmetic effect was significantly better in Purse string closure as compared to Linear skin closure. Wound infection was also less common in Purse string closure as compared to Linear skin closure but difference was not statistically significant.